2023
DOI: 10.3390/lubricants11030117
|View full text |Cite
|
Sign up to set email alerts
|

Wear Development in Oscillating Rolling Element Bearings

Abstract: Rotor blade bearings enable rotor blades to pivot about their longitudinal axis and thus control the power output and reduce the loads acting on the wind turbine. Over a design period of 20 years, rolling bearings are exposed to frequent oscillation movements with amplitude ratios of x/2b > 1, especially due to new control concepts such as Individual Pitch Control, which can lead to wear and a reduction in service life. The objective of this paper was to identify the dominant wear mechanisms and their conse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…A broader evaluation of the test is not available. Furthermore, a direct link between the change in surface roughness and friction torque is not reasonable, as can be seen by Wandel et al [32]. After the initiation of damage by a lack of lubricant, several wear mechanisms can occur in succession.…”
Section: Discussionmentioning
confidence: 99%
“…A broader evaluation of the test is not available. Furthermore, a direct link between the change in surface roughness and friction torque is not reasonable, as can be seen by Wandel et al [32]. After the initiation of damage by a lack of lubricant, several wear mechanisms can occur in succession.…”
Section: Discussionmentioning
confidence: 99%
“…In the second test run 140 sequences have more than 1000 cycles. Wandel et al reported on clearly visible wear in oscillating ball bearings after 1000 6 cycles at a contact pressure of 2 GPa [22]. Each test consists of several million sample points, which causes complete plots to provide little useful information.…”
Section: Test Programsmentioning
confidence: 99%